Pengaruh Tingkat Self-Esteem dan Fear Of Missing Out (FoMo) terhadap Kondisi Psychological Well-Being pada Siswa SMK X Bandung - Azzahra Putri Gumilar; Rifqi Farisan Akbar (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of social media use among vocational high school students has increased concerns about psychological well-being, particularly in relation to self-esteem and Fear of Missing Out (FoMO). Students are increasingly exposed to social comparison and digital pressure, which may affect their mental functioning. This study aims to examine the relationships between self-esteem, FoMO, and psychological well-being among vocational high school students in Bandung. A quantitative correlational design was employed, involving 80 students selected through purposive sampling. Data were collected using standardized self-esteem, FoMO, and psychological well-being scales, and analyzed using descriptive statistics, Pearson correlation, and classical assumption testing. The results indicate that self-esteem is positively and significantly correlated with psychological well-being, while FoMO shows a strong negative correlation with psychological well-being. In addition, self-esteem is found to be negatively associated with FoMO. These findings suggest that self-esteem functions as a protective factor, whereas FoMO acts as a psychological risk factor for students’ well-being. The study highlights the importance of strengthening internal psychological resources and managing digital-related anxiety to support students’ psychological well-being in the context of increasing social media exposure.